2022
DOI: 10.1111/jocn.16183
|View full text |Cite
|
Sign up to set email alerts
|

Balancing responsibilities, rewards and challenges: A qualitative study illuminating the complexity of being a rapid response team nurse

Abstract: Aim and Objective: To explore Rapid Response Team nurses' perceptions of what it means being a Rapid Response Team nurse including their perceptions of the collaborative and organisational aspects of the rapid response team (RRT).Background: For more than 20 years, RRT nurses have been on the frontline of critical situations in acute care hospitals. However, a few studies report nurses' perceptions of their role as RRT nurses, including collaboration with general ward nurses and physicians. This knowledge is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Implementing and maintaining RRT and RRS has been identified to be a complex process influenced by multiple factors (Rihari‐Thomas et al, 2017). Various research approaches have been applied to explore general ward nurses' experiences of the RRT and the RRS and report both barriers and facilitators for a satisfactory use of both team and system (Chua et al, 2017; Padilla et al, 2018), whereas a qualitative study of RRT‐nurses' perception of their function found their task to be complex and comprising responsibility, rewards and challenges (Bunkenborg et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Implementing and maintaining RRT and RRS has been identified to be a complex process influenced by multiple factors (Rihari‐Thomas et al, 2017). Various research approaches have been applied to explore general ward nurses' experiences of the RRT and the RRS and report both barriers and facilitators for a satisfactory use of both team and system (Chua et al, 2017; Padilla et al, 2018), whereas a qualitative study of RRT‐nurses' perception of their function found their task to be complex and comprising responsibility, rewards and challenges (Bunkenborg et al, 2022).…”
Section: Introductionmentioning
confidence: 99%